2018
DOI: 10.13177/irpa.a.2018.14.1.9
|View full text |Cite
|
Sign up to set email alerts
|

The Icelandic news media in times of crisis and change

Abstract: The news media around the world has experienced drastic changes in recent decades, and the Icelandic media is no exception. These changes originate in political, economic and not least technological developments. In this article we map key developments in the Icelandic media system and illustrate the changes it has undergone in the first decades of the 21st century. Journalism and media studies are under-researched fields of study in Iceland, and the country is usually absent from comparative work in these fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Aside from the size issue, recent research has shown how Iceland differs from the other Nordic states in numerous ways when it comes to its political and media systems (cf. Jóhannsdóttir & Ólafsson, 2018).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the size issue, recent research has shown how Iceland differs from the other Nordic states in numerous ways when it comes to its political and media systems (cf. Jóhannsdóttir & Ólafsson, 2018).…”
Section: Notesmentioning
confidence: 99%
“…One frequent area of exclusion in the literature on media and communication in the Nordic countries is research from Iceland -a country that is routinely absent from comparative studies. Despite this, it is often mentioned alongside the other four, much larger, Nordic countries and defined as some sort of "Nordic model" (Jóhannsdóttir & Ólafsson, 2018). This is not without its problems.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded local papers, since COVID-19 has commonly been a national news story. 2 As the Icelandic media landscape is quite small (Ólafsson & Jóhannsdóttir 2021;Jóhannsdóttir & Ólafsson 2018), we could include a high proportion of news media outlets, resulting in a good reflection of the Icelandic media. More specifically, we included the following outlets: Morgunblaðið, Mbl.is, Stöð 2, Fréttablaðið, Frettabladid.is, Stundin, Stundin.is, Kjarninn.is, Viljinn.is, Utvarpsaga.is, RÚV, Ruv.is, Rás 1, Rás 2, DV, DV.is, Viðskiptablaðið, Vb.is, Frettatiminn.is, Bylgjan, and Visir.is.…”
Section: Methodsmentioning
confidence: 99%
“…The Icelandic media system has been shown to possess the important qualities of a hybrid system with old and new media logics simultaneously at work (Guðmundsson 2019). However, the small size of the Icelandic media market has intensified the impact of the megatrends and made the country even more sensitive to them than is the case in larger societies (Guðmundsson 2018;Jóhannsdóttir & Ólafsson 2018). Icelandic media was hit hard by the financial crisis of 2008 and although media companies faced some financial difficulties before the crisis, difficulties have been felt even more acutely ever since.…”
Section: Stjórnmál and Stjórnsýslamentioning
confidence: 99%
“…Although a high number of journalists retained their membership after layoffs, the number of members shrank from 638 in 2007 to 566 in 2012 and there were only 569 members in April 2020, considerably lower than in 2007 (Blaðamaðurinn 2007. The Icelandic media market is thus economically vulnerable and ownership transitions, mergers and volatility has been particularly evident (Jóhannsdóttir & Ólafsson 2018). The annual balance sheets for example for 2018 of most media companies in Iceland reported losses and even though departments in some of the companies showed profit that did not change the general picture (Björnsson 2019).…”
Section: Stjórnmál and Stjórnsýslamentioning
confidence: 99%